2016
DOI: 10.1074/jbc.m115.713495
|View full text |Cite
|
Sign up to set email alerts
|

Actin-interacting Protein 1 Promotes Disassembly of Actin-depolymerizing Factor/Cofilin-bound Actin Filaments in a pH-dependent Manner

Abstract: Actin-interacting protein 1 (AIP1) is a conserved WD repeat protein that promotes disassembly of actin filaments when actin-depolymerizing factor (ADF)/cofilin is present. Although AIP1 is known to be essential for a number of cellular events involving dynamic rearrangement of the actin cytoskeleton, the regulatory mechanism of the function of AIP1 is unknown. In this study, we report that two AIP1 isoforms from the nematode Caenorhabditis elegans, known as UNC-78 and AIPL-1, are pHsensitive in enhancement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…In addition, another report shows that WDR1 might simply compete with Cofilin and dissociate redundant Cofilin from F-actin to accelerate severing activity (44). Furthermore, this regulation of Cofilin severing activity is dependent on the pH (46). In our study, we found WDR1 regulated Cofilin phosphorylation through LIMK1 to control the binding of Cofilin with actin filaments.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, another report shows that WDR1 might simply compete with Cofilin and dissociate redundant Cofilin from F-actin to accelerate severing activity (44). Furthermore, this regulation of Cofilin severing activity is dependent on the pH (46). In our study, we found WDR1 regulated Cofilin phosphorylation through LIMK1 to control the binding of Cofilin with actin filaments.…”
Section: Discussionsupporting
confidence: 52%
“…The binding of cofilin to cortactin is one of the mechanisms of cofilin inactivation which is typical for podosomes and invadopodia, actin-based dynamic protrusions produced by invasive cancer cells, vascular cells, and macrophages [ 124 , 125 ]. Actin-interacting protein 1 (AIP1) and cyclase-associated protein 1 (CAP1) promote the disassembly of cofilin-bound actin filaments [ 126 , 127 ]. Coronin provides recruiting cofilin to filament sides and thus enhances actin filament severing [ 128 ].…”
Section: Actin-depolymerizing Factor/cofilin Superfamilymentioning
confidence: 99%
“…WD40 has important roles in histone recognition, chromatin function, RNA processing and transcriptional regulation (Suganuma et al, 2008). WD repeat domain-containing proteins, such as AIP1, disassemble the actin filaments decorated with ADF and shorten the ADF-severed actin filaments, thus maintaining a high concentration of cellular actin monomers (Nomura et al, 2016). The adenylyl cyclase-associated protein (OsACP) is highly implicated in positive regulation of actin turnover process (Ono, 2013) as an actin-sequestering protein.…”
Section: Discussionmentioning
confidence: 99%